Integrating Mindfulness in Public and Nonprofit Education Programs to Foster Social Equity. (3rd September 2022) - Irizarry, Jose Luis
Abstract: As a discipline, the path forward for Public Administration from its role in creating, maintaining, and perpetuating systemic racism and social inequities is to promote social equity as part of the 4Es—engagement, empathy, equity, and ethics. This article proposes a fusion of mindfulness with the treatment of social equity, diversity, and inclusion (SEDI) in public and nonprofit administration as a promising strategy for improving the training of professionals to be competent in social equity. The goal is to encourage faculty to incorporate mindfulness principles and practices in their pedagogy, course design, course policies, and course activities in ways that foster mindfulness and social equity. To meet this challenge, faculty will need to (1) identify and reflect on the guiding principles of the field, and (2) incorporate mindful awareness in how professional values are conveyed by faculty within a subject matter where the intent is not to and the impact does not result in (a) alienating, shaming, or oppressing those with uninformed and/or stereotypical deeply held ideologies, while (b) simultaneously challenging students to intentionally tackle difficult conversations and ideologies.